A Kantian argument against comparatively advantageous genetic modification. Issue 8 (12th May 2011) - Jensen, David
Abstract : The genetic modification of children is becoming a more likely possibility given our rapid progress in medical technologies. I argue, from a broadly Kantian point of view, that at least one kind of such modification—modification by a parent for the sake of a child's comparative advantage—is not rationally justified. To argue this, I first characterize a necessary condition on reasons and rational justification: what is a reason for an agent to do an action in one set of circumstances must be a reason for any in those circumstances to do the action. I then show that comparatively advantageous genetic modification violates this principle since a child's "getting ahead" through genetic modification cannot be rationally justified unless other children also could receive the modification, thus rendering the advantage useless. Finally, I consider the major objection to this conclusion: it seems to disallow all cases of a parent's helping a child get ahead, something that parents normally engage in with their children. I argue that typical practices of developing a comparative advantage in a child, as well as practices of societal competition in general, do not conflict because they involve circumstances that mitigate the universal character of reasons. Many ordinary cases of competitive advantage that we think of as unjust, in fact, can be explained by my argument.